Global research trends in palliative care for breast cancer from 2012 to 2022: A scientometric analysis - Sun, Yixian; Wu, Jinyao; Tian, Huiting; Qiu, Xiuhua; Fang, Ying; Xiao, Yingjie; Zheng, Jiehua; Zhou, Yanqiong (Frontiers in Oncology, 2023)
Purpose We used bibliometric methods to evaluate the global scientific output of palliative care breast cancer research and to explore the current status and further research directions in the field over the past decade. Methods All relevant publications from the year 2012 to 2022 were retrieved from Web of Science. We applied VOSviewer and Bibliometrix R v4.2.1 to obtain information on subject domains, annual publication output and citations, countries and authors with the highest productivity, influential journals and articles, and popular keywords. Results In total, 1529 publications were included in the final analysis. Health services and supportive care, pain and symptom management were the focus of the research in the field. From the year 2017 to 2021, the annual publication output was abundant and peaked in 2018. The systematic review by Fitzmaurice et al. in 2017 was the most-cited publication. The United States was the leading country with the maximum number of publications, citations, and link strengths with other countries. The most contributing institution was University of Toronto. E. Bruera was the most prolific author, ranking first among the authors in both the H and M index. The journal with the most publications was Palliative & Supportive Care. Keywords analysis indicated that exploring the significant degree of palliative care to reduce anxiety and depression in breast cancer patients may be a good research direction. In addition, how to assess the optimal timing of palliative care interventions and further exploring the specific contradiction between insufficient medical resources and palliative care are also possible research directions. Conclusion Palliative care plays an important role in the treatment of breast cancer. With the help of a scientometric analysis in this field, researchers can clarify the current research status and hotspots worth fully exploring.